Complexity of the processes of modern urban - P. Bartkovyak; K. Kshakevich (E-Management)
The current crisis is primarily related to the economic situation in some countries. An economic aspect of the functioning of national economies, including the problem of the dynamics of gross domestic product, economic growth of quantitative (quantitative) character and economic development, which takes a qualifying (qualitative) character, as well as other indicators that describe the current economic situation have been analyzed in the article. This analysis allows us to determine whether this country is in a phase of growth or development, or in a phase of crisis, which can be understood synthetically as a decrease in production in the economy that lasts longer than two quarters.The crisis, however, from a different point of view has been analyzed in the research, a completely different matter of the crisis has been presented, and not its economic aspect . Continuous growth or economic development should theoretically сontribute for improving the quality of people’s life. Economic growth in the national economy on a “macro” scale leads to the growth and development of individual households, which in a simplified form can be called an increase in prosperity. The same expectations of society - economic growth should affect the improvement of living conditions of the ordinary citizen. A similar situation should look like during the economic crisis. Times of macroeconomic crisis - the crisis also of the individual household, the need to “tighten the belt.” However, in times of economic prosperity, a person is also forced to function in parallel in a crisis, that affects every major city, regardless of the growth or crisis of the national economy, lack of jobs, production cuts, rising unemployment, etc. Here we are talking about a specific crisis, which reveals itself in the worsening of the quality of the environment of human functioning - the environment in which a person is daily and meets his needs.